Mengestimasi Expected Default Probability dan Credit Risk Spread Menggunakan Model KMV Merton: Studi Kasus Bank Islam Malaysia Berhad - Septiana, Nurul Izzati; Katri, Fatin Salwa Binti Haji; Ideris, Azlina Binti; Noryatim, Nadiana (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2025)
The objective of the paper is to estimate the expected default probability and credit risk spread of Bank Islam Malaysia using the KMV Merton Model and analyse the strengths of the KMV model. The data used in this research are short term and long-term liabilities data of Bank Islam Malaysia Berhad that we obtained from the financial statements, stock prices and number of stocks traded of BIMB and Islamic Bank-relevant interest rates data that we obtained from the Overnight Policy Rate Decision (OPR) by Bank Negara Malaysia. The data is then prepared and interpolated to match weekly period before applying the KMV Model using Microsoft Excel to calculate the default probability and credit risk spread of BIMB. The result shows that the Probability of Default for BIMB is nearly 0.0001 for the first 3 years of its debt maturity period and nearly 0.0007 and 0.002 for the maturity period of 4 and 5 years respectively. Credit risk spread for BIMB is nearly null for the first 2 years maturity period then gradually increases each year to 0.01, 0.05 and 0.14. BIMB’s distance to default ranges between 9.17-10.01. The research indicates that the BIMB’s calculated PD is reliable and that the KMV Merton Model provides high accuracy and reliability of credit risk measurements. The KMV Model can be applied to different types of companies including Islamic Bank.